Acoustic emission studies for characterization of fatigue crack growth behavior in HSLA steel. Issue 1 (2nd January 2016) - Kumar, Jalaj; Ahmad, S.; Mukhopadhyay, C.K.; Jayakumar, T.; Kumar, Vikas
Abstract: High strength low alloy (HSLA) steels are a group of low carbon steels and used in oil and gas pipelines, automotive components, offshore structures and shipbuilding. Fatigue crack growth (FCG) characteristics of a HSLA steel have been studied at two different stress ratios ( R = 0.3 and 0.5). Acoustic emission (AE) signals generated during the FCG tests have been used to understand the FCG processes. The AE signals were captured by mounting two piezoelectric sensors on compact tension specimens in liner location configuration. The AE generated in stage II of the linear Paris region of FCG has been attributed to the presence of two sub-stages with two different slopes. The AE generated at higher values of stress intensity factor is found to be useful to identify the transition from stage II to stage III of the FCG. AE location analysis has provided support for increased damage at the crack tip for higher stress ratio. The peak stress intensity ( K max ) values at the crack tip have shown good correlation with the transitions from stage IIa to stage IIb and stage II to stage III of the FCG for the two stress ratios.